65.2k views
1 vote
Find the product. (3p^4)^3 · (p^2)^7

User Wenyi
by
5.4k points

1 Answer

1 vote

Answer:
27p^(26)

Explanation:

In this case, you need to use the Power of a power property, which states that:


(a^m)^n=a^(mn)

And the Product of powers property, which states that:


(a^m)(a^n)=a^((m+n))

Then, applying this, we get the following product:


(3p^4)^3*(p^2)^7=27p^((4)(3))*p^((2)(7))=27p^(12)*p^(14)=27p^((12+14))=27p^(26)

User Karim Manaouil
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.